A combined experimental and theoretical investigation of the excited-state dynamics of 2, 4, 6-trinitrotoluene (TNT) in DMSO solvent. Issue 36 (13th September 2021) - Liu, Runze; Shang, Fangjian; Xiong, Ying; Zhang, Chaoyang; Yang, Songqiu; Zhou, Panwang; Liu, Jianyong
Abstract : In the present contribution we carried out a TDDFT and femtosecond transient absorption study of the excited state dynamics of TNT in DMSO solvent. Abstract : In the present contribution we carried out a TDDFT and femtosecond transient absorption study of the excited state dynamics of TNT in DMSO solvent. Vertical excitation and excited state relaxation were calculated at the SMD/M06-2X/TZVP level of theory. The electron absorption spectrum for the DMSO solvated TNT was calculated and compared with the experimental results. The results of the electronic excitation energies and the spin–orbital constants imply an intersystem crossing for the S1 –T2 transition. The femtosecond time-resolved transient absorption measurements of the TNT in DMSO show the presence of two absorption signals around 650 nm and 540 nm, which are assigned to the population in the lowest singlet and triplet excited states, S1 and T1, respectively. The fast decay of the S1 state population is assigned to an efficient S1 –T2 intersystem crossing, which soon internally converts to the T1 state. The slow decay of the T1 population is attributed to the nonradiative transition to the S0 state. The combined theoretical and experimental results present a mechanistic view of the photophysical dynamics of TNT in DMSO solution.